Top disconnection versus base disconnection in structures subjected to harmonic base excitation. (1st December 2017) - Fabrizio, Cristiano; Di Egidio, Angelo; de Leo, Andrea M.
Highlights: Archetype model describing the base isolation and the tuned mass damper schemes. Parameters able to describe continuously the system from the BI to the TMD scheme. Maps describing the effectiveness of base isolation and tuned mass damper schemes. Choice of the design parameters inside the gain regions of both the behaviour maps. Abstract: Aim of the present study is to investigate the opportunity of improving the dynamic response of a structure by making an intermediate disconnection through it. In this context it is of interest to wonder if the disconnection works mainly as tuned mass damper for the lower structure or it works mainly as base isolation for the upper structure. This paper is the first stage of this study. An archetype model, constituted by a simple two-degree of freedom system, has been taken as representative of structures provided with a disconnection, where a base isolation or a tuned mass damper scheme is used. The system has a constant total mass, while stiffness and mass ratios are taken as variable parameters. Two parameters capable of evaluating the efficiency of the disconnection, called the gain indicators, have been introduced, being the system subjected to an harmonic base excitation. Two different types of behavior maps, one referring to the base isolation and the other to the tuned mass damper, have been obtained. In these maps the regions where a base isolation or a tuned mass damper system works properly are well recognizable and it is also possible to point out some other regions of the parameters space where both systems work well.